2010
DOI: 10.1002/chem.201000849
|View full text |Cite
|
Sign up to set email alerts
|

The Conformational Landscape of Nicotinoids: Solving the Conformational Disparity of Anabasine

Abstract: The conformational landscape of the alkaloid anabasine (neonicotine) has been investigated by using rotational spectroscopy and ab initio calculations. The results allow a detailed comparison of the structural properties of the prototype piperidinic and pyrrolidinic nicotinoids (anabasine vs. nicotine). Anabasine adopts two most stable conformations in isolation conditions, for which we determined accurate rotational and nuclear quadrupole coupling parameters. The preferred conformations are characterized by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…The crystal structure of o-vanillin detected only the most stable conformation, offering no information on higher-energy structures. Moreover, crystal structures are dominated by intermolecular interactions, so they do not always correspond to the preferred structures of the molecule [6,30]. Alternatively, rotational spectroscopy offers a detailed molecular description, disentangling the intrinsic factors controlling conformation and structure.…”
Section: Discussionmentioning
confidence: 97%
“…The crystal structure of o-vanillin detected only the most stable conformation, offering no information on higher-energy structures. Moreover, crystal structures are dominated by intermolecular interactions, so they do not always correspond to the preferred structures of the molecule [6,30]. Alternatively, rotational spectroscopy offers a detailed molecular description, disentangling the intrinsic factors controlling conformation and structure.…”
Section: Discussionmentioning
confidence: 97%
“…13 The electron diffraction pattern was reproduced by assuming a mixture of two distinct conformers of nicotine. Studies of the nicotine analogues 2-phenylpyrrolidine 14 and anabasine 15 have been recently reported. The former has been studied in gas and solution-phase using MW, electronic and NMR spectroscopic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…3, reproduce those previously proposed for (−)-S-anabasine in Ref. [35] Cartesian coordinates of the eight conformers (B3PW91/aug-cc-pVTZ, gas phase) are available as supplementary material (Table S3).…”
Section: Displays a Schemementioning
confidence: 85%
“…At this point, it is worth to mention that authors in Ref. [35] also suggested that an N. . .H HBi may be responsible for the observed deviation from the ideal pyridine ring orientation in the two main conformers, namely m01 and m02.…”
Section: Data Reported Inmentioning
confidence: 95%
See 1 more Smart Citation